The Impact of Technological Innovation on Consumer Decision Making: A Qualitative Analysis in the Gadget Industry - Ackhriansyah Achmad Gani; Mahatir Mohammad; Sahari Jafar; Pratiwi Juniar Achmad Gani (Universitas Dharma Wacana, 2022)
This study aims to analyze the impact of technological innovation on consumer decision-making in the gadget industry. Using a qualitative approach, this research involves interviews with consumers in various innovation adoption groups, which include innovators, early adopters, early majority, late majority, and slow followers. In addition, this research also studied the concept of consumer satisfaction and how consumer satisfaction with technological innovations affects purchasing decisions in the gadget industry. Through in-depth interviews with consumers, this research generated rich insights into consumers' experiences of adopting technological innovations, factors that influence purchase decisions, and the role of consumer satisfaction in the decision-making process. Qualitative data analysis was conducted to identify patterns, themes, and relationships between the variables studied. The results of this study show that understanding the level of consumer adoption in technological innovation is of key importance for gadget companies. Innovator and early adopter consumers tend to have higher risk, are enthusiastic in trying new technology, and play an important role in influencing others to adopt the innovation. Meanwhile, early majority consumers have a slower adoption rate, but their purchasing decisions are influenced by testimonials from previous adoption groups. Consumer purchase decisions in the gadget industry are also influenced by their satisfaction with technological innovations. Consumers who are satisfied with the user experience of an innovation are likely to recommend it to others and consider purchasing products with similar innovations. Therefore, gadget companies need to pay attention to product development that meets consumer expectations, provides a positive user experience, and provides responsive customer service.